Second‐Generation Inhibitors of the Mitochondrial Permeability Transition Pore with Improved Plasma Stability. (25th September 2019) - Šileikytė, Justina; Devereaux, Jordan; de Jong, Jelle; Schiavone, Marco; Jones, Kristen; Nilsen, Aaron; Bernardi, Paolo; Forte, Michael; Cohen, Michael S.
Abstract: Excessive mitochondrial matrix Ca 2+ and oxidative stress leads to the opening of a high‐conductance channel of the inner mitochondrial membrane referred to as the mitochondrial permeability transition pore (mtPTP). Because mtPTP opening can lead to cell death under diverse pathophysiological conditions, inhibitors of mtPTP are potential therapeutics for various human diseases. High throughput screening efforts led to the identification of a 3‐carboxamide‐5‐phenol‐isoxazole compounds as mtPTP inhibitors. While they showed nanomolar potency against mtPTP, they exhibited poor plasma stability, precluding their use in in vivo studies. Herein, we describe a series of structurally related analogues in which the core isoxazole was replaced with a triazole, which resulted in an improvement in plasma stability. These analogues were readily generated using the copper‐catalyzed "click chemistry". One analogue, N ‐(5‐chloro‐2‐methylphenyl)‐1‐(4‐fluoro‐3‐hydroxyphenyl)‐1 H ‐1, 2, 3‐triazole‐4‐carboxamide (TR001 ), was efficacious in a zebrafish model of muscular dystrophy that results from mtPTP dysfunction whereas the isoxazole isostere had minimal effect. Abstract : Our first‐generation mitochondrial permeability transition pore (mtPTP) inhibitors, such as63, suffer from suboptimal mouse plasma stability. Herein we describe design, synthesis and in vitro characterization of triazole‐based second‐generation mtPTP inhibitors with significantly improved mouse plasma stability. Further, we validate the therapeutic potential of newly synthetized inhibitorTR001 in a zebrafish model of muscular dystrophy.